Typical methods of collecting evidence in the investigation of crimes against civil equality - Troyanov, Tihomir (Law Journal of New Bulgarian University, 2023)
The article examines the typical methods of investigating crimes against the equality of citizens, identifying the most frequently collected evidence to clarify the circumstances of the case, related to this legal qualification.